2022
DOI: 10.1007/s43657-021-00038-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and Sex-Biased Fluctuation of Birth Weight in Tibetan Populations

Abstract: Birth weight (BW) is a key determinant of infant mortality. Previous studies have reported seasonal fluctuation of BW. However, the responsible environmental factors remain disputable. High-altitude environment provides a great opportunity to test the current hypotheses due to its distinctive climate conditions. We collected BW data of ~ 9000 Tibetan singletons born at Lhasa (elevation: 3660 m) from 2014 to 2018. Using regression models, we analyzed BW seasonality of highland Tibetans. Multivariate models with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Therefore, we speculate that the selective pressure on EPAS1 is likely through its effect on hemoglobin, rather than directly on the reproductive traits. The down-regulation of EPAS1 in placenta likely reflects a blunted hypoxic response that may improve vasodilation of UC for better blood flow, and eventually leading to the higher BW in Tibetans (He et al, 2023 ). For EGLN1, another well-known gene in Tibetans, we detected between-population expression difference in the male UC layer, but not in other placental layers.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Therefore, we speculate that the selective pressure on EPAS1 is likely through its effect on hemoglobin, rather than directly on the reproductive traits. The down-regulation of EPAS1 in placenta likely reflects a blunted hypoxic response that may improve vasodilation of UC for better blood flow, and eventually leading to the higher BW in Tibetans (He et al, 2023 ). For EGLN1, another well-known gene in Tibetans, we detected between-population expression difference in the male UC layer, but not in other placental layers.…”
Section: Discussionmentioning
confidence: 76%
“…Han Chinese moving to high altitude), reflected by the higher newborn BW and the lower prenatal and postnatal mortality (Beall et al, 2004 ;Moore et al, 2011 ). As expected, Tibetans performed better than Han migrants during fetal development (He et al, 2023 ;Julian et al, 2009 ;Moore et al, 2011 ;Moore et al, 2001a ). Previous genomic studies have identified a group of genes potentially contributing to the genetic adaptation of Tibetans to high-altitude environments, and these studies were mostly focused on the blood and cardiopulmonary systems of adult Tibetans (Beall et al, 2010a ;Bigham et al, 2010 ;Deng et al, 2019 ;Peng et al, 2011 ;Simonson et al, 2010 ;Song et al, 2020 ;Xiang et al, 2013 ;Xu et al, 2011 ;Yang et al, 2017 ;Yi et al, 2010 ).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations